Factor Analysis Considered by Entrepreneurial Student at UMM - Fien Zulfikarijah (Journal of Career and Entrepreneurship, 2022)
The purpose of the study was to determine the factors considered in entrepreneurial students at UMM. The research population is UMM students who are entrepreneurs, a sample of 100 from 10 faculties with a total of 10 students per faculty. The analysis tool used is factor analysis with 34 research variables. The results showed that of the 34 were selected variables, 22 variables were classified into 4 factors, namely the readiness to work, the independence, earning greater income and the life balancing. It means that students in entrepreneurship consider the readiness to work, the independence, earning the higher income and the life balancing. The dominant factor considered is the readiness to work.